Factors affecting an investor's purchasing intention on Islamic financial products - Tan, Rui Teck (2012)
Our study aims to establish the factors that affect an investor’s decision to invest in Islamic financial products in Singapore. Our study is based on Central Provident Fund (CPF) holders, assuming that they have the avenue to invest in financial products via their CPF accounts.